Development of Maintenance Management System for Himreen Dam Project - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
The concept of the modern maintenance management has been developed inparallel with the international development of the science and technology, especiallytargets identification of the management, and it’s duties in the hydraulicestablishments.The research included a real state study of maintenance management activitiesof Himreen dam to propose a suitable maintenance management system. Also itpresented a description of the dam importance and discussed the concept of themodern maintenance; definition, classification, and the analysis of the four factors ofmanagement system which are (planning, organizing, directing and controlling).The field survey included preparing the questionnaire list, conducting thestatistical analysis for it’s axes, and discussing the results.Many conclusions and recommendations have been deduced which related tothe applications of the maintenance management in the dam project, and to generalizethe proposed system in future to all dam’s projects in Iraq.